Physical Activity Engagement in Young People with Down Syndrome: Investigating Parental Beliefs. Issue 1 (5th October 2015) - Alesi, Marianna; Pepi, Annamaria
Abstract : Background: Despite the wide documentation of the physical/psychological benefits derived from regular physical activity (PA), high levels of inactivity are reported among people with Down syndrome. This study aims to explore parental beliefs concerning involvement, facilitators/barriers and benefits of PA in young people. Method: Semi‐structured interviews were conducted with 13 parents of young people with Down syndrome. Results: Three facilitation themes were identified: (i) the support derived from family; (ii) the availability of APA (Adapted Physical Activity) expert instructors and coaches; (iii) the challenging nature of sport activities. Three barrier themes were identified: (i) the lack of APA expert coaches and specialized gyms; (ii) the characteristics of Down syndrome; and (iii) the parental beliefs and worries. Conclusions: Family plays a key role, as facilitator and barrier, to the participation of their children with Down syndrome in PA. Crucial is the implementation of evidence‐based exercise programmes involving people with Down syndrome and their families.